Foreground simulations for observations of the global 21-cm signal - Klutse, Diana (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2019)
The sky-averaged (global) spectrum of the redshifted 21-cm line promises to be a direct probe of the Dark Ages, the period before the first luminous sources formed and the Epoch of Reionization during which these sources produced enough ionizing photons to ionize the neutral intergalactic medium. However, observations of this signal are contaminated by both astrophysical foregrounds which are orders of magnitude brighter than the cosmological signal and by non-astrophysical and non-ideal instrumental effects. It is therefore crucial to understand all these data components and their impacts on the cosmological signal, for successful signal extraction. In this view, we investigated the impact that small scale spatial structures of diffuse Galactic foreground has on the foreground spectrum as observed by a global 21-cm observation. We simulated two different sets of observations using a realistic dipole beam model of two synchotron foreground templates that differ from each other in the small scale structure: the original 408 MHz all-sky map by Haslam et al. (1982) and a version where the calibration was improved to remove artifcats and point sources (Remazeilles et al., 2015). We generated simulated foreground spectra and modeled them using a polynomial expansion in frequency. We found that the different foreground templates have a modest impact on the simulated spectra, generate differences up to 2% in the root mean square of residual spectra after the log-polynomial best fit was subtracted out.
Keywords: Cosmic background radiation; Astronomy -- Observations; Electromagnetic waves; Radiation, Background